The Impact of Online Collaborative Writing Strategy via Google Docs on Senior High School Learners’ Writing Performance in Composing Narrative Texts - Zahrok, Aisyah; Rahmawati, Eva (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
Improving EFL learners’ narrative writing remains a persistent challenge, particularly when instruction relies heavily on individual writing tasks that limit peer interaction and cognitive engagement. Recent pedagogical debates underscore the need for socially interactive approaches to writing, which are supported by digital technologies. Grounded in Vygotsky’s Sociocultural Theory—particularly the Zone of Proximal Development—this study explores the use of collaborative writing via Google Docs as a means of scaffolding learners’ writing performance. A quasi-experimental design was conducted with two tenth-grade classes in Indonesia: an experimental group that used Google Docs collaboratively and a control group that received conventional instruction. Writing performance was assessed using an analytical rubric encompassing content, style, language use, organization, and mechanics. The results revealed that the experimental group achieved significant improvements, particularly in content development, organizational coherence, and language accuracy. The findings underscore that collaborative writing supported by digital tools and sociocultural learning principles contributes meaningfully to the development of learners’ narrative writing performance. Accordingly, it is recommended that EFL educators adopt technology-mediated collaborative writing strategies to facilitate more interactive, engaging, and pedagogically sound writing instruction.